If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 4 = -4 Reorder the terms: 4 + -4x = -4 Solving 4 + -4x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -4x = -4 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = -4 + -4 -4x = -4 + -4 Combine like terms: -4 + -4 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 2y+4=6y-6 | | 4350*.5= | | -20x^3+96x^2=0 | | -20x^3-96x^2=0 | | 9c*3=6 | | 49x^3-56x^2+16x=0 | | (5y^2-7y+3)+(-2y^2+4y+1)= | | 6p+4=2(2p+1) | | 10x+23(x-5)=182 | | 4(2x+1)=3(x+13) | | 12x^3+23x-24=0 | | 3.5b-33.4=75.5 | | 14p-10=8+2p | | 2g+14+5g=8-3+8 | | 12x-6=2x+7 | | 3(2x-1)+4=x+25 | | 14x-48=5x-3 | | 18-4x=7x-7 | | 2y-80=y+9 | | 2y-80=y+90 | | 10x-24=8x+12 | | X+30=2x | | 4[2x-5(x-3)]=6 | | 10-4x=6-2x | | 36+340=2 | | 7x(2)+x-8=0 | | 9x(x-2)=9x^2+40 | | 6w-14w=-72 | | -7(x+4)-11=16+8 | | 3(2x-5)+9=12 | | 20n=m | | m=20n |